Methodology framework for the design of digital ecosystems - Hadzic, Maja; Chang, Elizabeth; Dillon, Tharam S. (IEEE, 2007)
Digital Ecosystems have recently been introduced into the computer and information societies. Digital Ecosystem (DES) is the dynamic and synergetic complex of digital communities consisting of interconnected, interrelated and interdependent Digital Species (DS) situated in a Digital Environment (DE) that interact as a functional unit and are linked together through actions, information and transaction flows. DES ranspose mechanisms from living organisms like autonomy, viability and self-organisation to arrive at novel knowledge and architectures. The proposed DES embraces a number of different technologies such as ontologies, agent-based and self-organizing systems etc. The synergetic effects of these methodologies results in a more efficient, effective, reliable and secure system. DES is still in its early implementation phase. No clear methodology for digital ecosystem design exists yet.In this paper, we propose a methodological framework that consists of five phases and addresses many different aspects of the DES design. In this methodology, we focus on the key factors associated with the DES design such as roles of different digital components within the DES, organisation and collaboration of the digital components, their individual design along with intelligence and security within the DES. More details are introduced at each step and every sequential step takes the DES to a higher level of elaboration. This methodological framework allows better control over the design process and serves as a navigating tool during DES design.